Identification and Separation of Cannabis sativa, Embleia ribes, Myristica fragrans and Piper longum from Organic Extract on Silica Gel Surface with Anionic Micellar Solvent System : Application in Ayurvedic Medicine - Bhawani, Showkat Ahmad; Mohammad, A.; Sharma, S.; Singh, Ram B. (Bentham Open, 2010)
Cannabis sativa, Myristica fragrans, Piper longum and Embleia ribes are the active pharma ingredients of an ayurvedic herbal formulation Jatiphaldya, which is beneficial in many typical stomach related disorders. The present study is aimed to develop a simple and reliable thin layer chromatographic (TLC) method using micellar solution of sodium dodecyl sulfate (SDS) as mobile phase for the identification of all the four herbal drugs with preliminary separation on silica gel ‘G’ TLC plate. The active components of drug were extracted in a mixture of ethanol and water (4:1), chromatographed on silica gel TLC plate using aqueous SDS (5%) as mobile phase and the resolved spots for Cannabis sativa (RF-0.95), Myristica fragrans (RF-0.64), Piper longum (RF-0.41) and Embleia ribes (RF-0.26) were identified using vanillin-sulfuric acid (2% solution of vanillin in 5% methanolic sulfuric acid). In order to realize most favorable mobile phase system in combination with silica gel ‘G’ as stationary phase, the effect of nature of surfactants (anionic, cationic or nonionic) and the level of concentration of each surfactant [sodium dodecyl sulfate (SDS), N-cetyl-N, N, N-trimethylammonium bromide (CTAB) or t- octyl phenoxydacaethoxy ethanol (TX-100)] on the mobility of all four active components was examined. In addition, the effect of organic (urea and alkanols) and inorganic (NaCl) additives in 5% aqueous SDS solution on mobility pattern of active herbal pharma ingredients was examined. The presence of ammonia and nitrate in the drug sample was found to hamper the resolution and identification of all active components. However, NaCl, KCl and glucose do not offer serious interference.